2016
DOI: 10.1097/mph.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Use During Maintenance Therapy for Acute Lymphoblastic Leukemia Avoids Mercaptopurine-related Hepatotoxicity

Abstract: 6-Mercaptopurine (6-MP) is the mainstay of treatment for acute lymphoblastic leukemia and lymphoblastic lymphoma. It is metabolized into the pharmacologically active, 6-thioguanine nucleotide (6-TGN), and 6-methyl mercaptopurine nucleotides (6-MMPN), which is associated with hepatotoxicity that jeopardizes antileukemic therapy. Allopurinol alters the metabolism of 6-MP to increase 6-TGN levels and decreases 6-methyl mercaptopurine nucleotides levels. We report 2 cases in which combination therapy of allopurino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Both morning dosing and split dosing of 6‐MP led to a reduction in his 6‐MMP levels, but with a commensurate drop in the 6‐TGN levels (Figure A) with continued episodic hypoglycemia. After several weeks without substantial improvement, a trial of allopurinol was initiated, based on data suggesting that this could result in a more significant drop in 6‐MMP levels and reduction in associated symptoms . His 6‐MP dose was reduced to 25 mg/m 2 /day and allopurinol was started at 50 mg/m 2 /day daily.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both morning dosing and split dosing of 6‐MP led to a reduction in his 6‐MMP levels, but with a commensurate drop in the 6‐TGN levels (Figure A) with continued episodic hypoglycemia. After several weeks without substantial improvement, a trial of allopurinol was initiated, based on data suggesting that this could result in a more significant drop in 6‐MMP levels and reduction in associated symptoms . His 6‐MP dose was reduced to 25 mg/m 2 /day and allopurinol was started at 50 mg/m 2 /day daily.…”
Section: Resultsmentioning
confidence: 99%
“…Allopurinol when given with oral 6-MP inhibits first pass metabolism leading to a three-to fivefold increase in peak plasma concentration and plasma area under the curve 10 and can alter the metabolism of 6-MP, favoring the production of 6-TGN over 6-MMP. 6,11 Small series of leukemia patients have shown that the combination of allopurinol and reduced dose 6-MP is an effective strategy for the management of 6-MP-associated pancreatits 7 and hepatotoxicity. [5][6][7] Here, we employed this strategy for the man- In conclusion, this case series contributes to the scant existing literature regarding 6-MP-associated hypoglycemia in patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to modifying ROS levels, XOD is involved in the metabolism of several drugs. Recent reports suggest the utility of allopurinol to reduce chemotherapy toxicity in leukaemia patients [ 205 ]. An ongoing clinical trial is testing the feasibility of allopurinol to improve 6-mercaptopurine regimen in paediatric ALL treatment (NCT03022747, phase II).…”
Section: The Use Of Ros As a Therapeutic Target In Haematological Malmentioning
confidence: 99%